A technique to remove a well-fixed titanium-coated RM acetabular cup in revision hip arthroplasty - Judas, F (2011)
A major concern during revision hip arthroplasty is acetabular bone loss and bleeding during the extraction of well-fixed cementless acetabular cup, because no interface exists between the host bone and the cup. Forceful removal of such component using curved gouges and osteotomes often leads to extended bone loss and compromises reimplantation of a new socket. In the following case report, we removed a well-fixed polyethylene titanium-coated RM acetabular cup with 20 years of follow-up, by significant wear of the polyethylene layer. The isoelastic femoral stem was also removed by mechanical failure. We report a technique for removal of the cementless acetabular cup using powered acetabular reamers. The RM cup was sequentially reamed and when the polyethylene layer was thin enough, the remaining cup was removed easily by hand tools. The acetabular bone stock is preserved and the risks of bone fractures and bleeding are minimized. To our knowledge, these principles were applied only in cemented cups. We have used this technique in 10 cases with excellent results and no complications were noted. This is a simple, reproducible, non-costly, non-timing consuming, safe and successful technique to remove well-fixed titanium-coated RM acetabular cups.